Accounting and auditing practices of public sector units in India (Note) - Sikidar, Sujit (1994)
"The author takes a look at the features of accounting and audit practices pertaining to public sector units, as pointed out in CAG's audit reports. He covers their revenue structure, operations, valuation, adjustments for asserts/liabilities, etc., in the discussion"
Keywords: Note; Government business enterprises - Auditing - India; Government business enterprises - Accounting - India; Public sector - India; Public sector